Examining Loneliness and Social Anxiety in College Students Across Different Phases of the Pandemic - Signorelli, Jordan (My University, 2024)
Introduction: Emerging adulthood (18-25) is a stage of development full of profound changes. Emerging adults attending college are vulnerable to mental health challenges, such as loneliness and social anxiety. The pandemic put students at greater risk with research showing loneliness and social anxiety levels increased pre-pandemic to pandemic onset (greatest health risk and social behavior restrictions period), but none has examined these levels as the pandemic continued and health risk and restrictions decreased. Research reveals a positive relationship between loneliness and social anxiety pre-pandemic, but none has examined their relationship during the pandemic. Purpose: Aims include examining: 1) whether loneliness and social anxiety levels differ across three years following pandemic onset; and 2) if there are differences in the relationship between loneliness and social anxiety across these years. I hypothesize loneliness and social anxiety levels will be highest during the first year after onset and will be lowest during the third year after onset. Method: Repeated cross-sectional study included undergraduate participants at a public southeastern university recruited through Introductory to Psychology courses and random sample during three years following pandemic onset (2020-2023). Participants completed a two-part online survey including the UCLA Loneliness Scale and Social Phobia Screener. Results: The ANCOVA examining AY sample differences in mean ULS score approached significance, F(2,2905) = .232, p = .098. Post hoc pairwise comparisons were examined and showed the AY1 sample had significantly lower mean ULS scores (19.75) compared to the AY2 sample (20.36), p = .039. The ANCOVA examining AY sample differences in mean SPS scores was significant, F(2,2915) = 19.18, p < .001. Post hoc pairwise comparisons showed the AY1 sample had significantly lower mean SPS scores (3.70) compared to the AY2 sample (4.92) and AY3 sample (4.77) (ps < .001). The AY2 and AY3 samples did not significantly differ. Partial correlations revealed significant positive correlations between the ULS and SPS for AY1 (r = .413, p < .001), AY2 (r = .445, p < .001), and AY 3 (r = .436, p < .001). These correlations did not significantly differ when compared using r to z Fisher transformations (AY1 compared to AY2 p =0.20; AY2 compared to AY3 p =.40; AY1 compared to AY3 p=.28).  Discussion: The results show that college students’ levels of loneliness and social anxiety may have been influenced by the chronicity of the pandemic and the social reintegration when social restrictions lessened. This study helps in understanding the trajectory of and relationship between loneliness and social anxiety across pandemic phases in college students. This study can help guide future research in efforts to understand reasons for changes in loneliness and social anxiety, and the causal relationship between loneliness and social anxiety in college students. The longer-term impact of loneliness and social anxiety in college students found in this study suggests the need to attend to student mental health, especially as crises become more chronic.
Keywords: Loneliness; Social Anxiety; Pandemic